Pengaruh Media Flash Card Menggunakan Aplikasi Edukatif Wordwall Terhadap Kemampuan Kognitif Mengenal Huruf Hijaiyah Anak Kelompok B - Safira, Baiq Kamila; Gunawan, Gunawan; Astini, Baik Nilawati; Rachmayani, Ika (Indonesian Publication Center, 2025)
This study applies a quantitative approach, utilizing a pre-experimental design to assess cognitive abilities before and after using Flash Card media through the educational application Wordwall, with a sample size of 18 early childhood children. The research aims to analyze the effect of using Flash Card media via the Wordwall educational application on preschool children's cognitive ability in recognizing Hijaiyah letters. Recognizing Hijaiyah letters is crucial for children's cognitive development and initiating their understanding of the Quran, supported by previous studies highlighting cognitive challenges faced by many children in Indonesia. Data were collected through pre-tests and post-tests, documenting cognitive improvement measured by N-Gain scores. The results showed an average increase of 0.71, confirming the effectiveness of Flash Card media using the Wordwall educational application in enhancing cognitive abilities. Hypothesis testing with a t-test indicated a significant effect of Flash Card media using the Wordwall application on children's cognitive ability to recognize Hijaiyah letters. Thus, the use of the Wordwall educational application represents an innovative solution for interactive learning in early childhood education and contributes positively to cognitive development in recognizing Hijaiyah letters.